2011
DOI: 10.1073/pnas.1019224108
|View full text |Cite
|
Sign up to set email alerts
|

Pro-B cells sense productive immunoglobulin heavy chain rearrangement irrespective of polypeptide production

Abstract: B-lymphocyte development is dictated by the protein products of functionally rearranged Ig heavy (H) and light (L) chain genes. Ig rearrangement begins in pro-B cells at the IgH locus. If pro-B cells generate a productive allele, they assemble a pre-B cell receptor complex, which signals their differentiation into pre-B cells and their clonal expansion. Pre-B cell receptor signals are also thought to contribute to allelic exclusion by preventing further IgH rearrangements. Here we show in two independent mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…These data suggest that deficiency of NMD impairs early B-cell development coincident with the timing of nonsense transcript production. Similar results are reported in the accompanying paper by Lutz et al (42), which shows impaired B-cell development in mice expressing nonsense μHC transcripts that cannot be degraded by NMD.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These data suggest that deficiency of NMD impairs early B-cell development coincident with the timing of nonsense transcript production. Similar results are reported in the accompanying paper by Lutz et al (42), which shows impaired B-cell development in mice expressing nonsense μHC transcripts that cannot be degraded by NMD.…”
Section: Resultssupporting
confidence: 78%
“…Our data therefore suggest that stabilized TCR-β nonsense transcripts that only encode the variable domain, which cannot support pre-TCR assembly or signaling, may contribute to allelic exclusion. Although we cannot exclude the possibility that these effects may be mediated by other functions of the NMD pathway or Rent1/hUpf1 itself, this model is supported by recent observations that stable but nonproductive μHC transcripts can suppress VDJ recombination in pro-B cells (42). A prior study had failed to observe phenotypic consequence after expression of a TCR-β message with a physiological frameshift mutation in the DβJβ region that could not derive functional TCR-β protein (43).…”
Section: Discussionmentioning
confidence: 62%
“…Although we demonstrate that many amino acid transporter mRNAs are direct and/or indirect targets of NMD, at least neutral amino acid transport is not upregulated by the inhibition of NMD, despite an increase in the mRNAs encoding the SNAT2 transporter. While we have not ruled out the possibility that other amino acids have their transport and/or metabolism directly regulated by NMD, our findings emphasize that the biological significance of an mRNA's degradation by NMD must be verified with evidence either that the protein is similarly regulated or that the stabilized mRNA has a biological function (as suggested for truncated antibody and T-cell receptors [14,25]). …”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, almost none of the peripheral B cells carried NP V H DJ H rearrangements, and we suggested that the reduced activity of RAG1 delayed rearrangement of the second locus and forced the B cells into apoptosis (33). Furthermore, it has previously been demonstrated that normal pro-B cells are capable of sensing the difference between a P and an NP V H DJ H rearrangement already at the transcriptional level (34). Perhaps a disadvantage caused by noncoding mH mRNA leading to cell death could explain why B cells carrying NP V H DJ Hrearrangements are not observed as frequently in the periphery as predicted.…”
Section: Discussionmentioning
confidence: 97%